Thiazolidin-4-one-based compounds interfere with the eicosanoid biosynthesis pathways by mPGES-1/sEH/5-LO multi-target inhibition - Ester Colarusso; Marianna Potenza; Gianluigi Lauro; Maria Giovanna Chini; Valentina Sepe; Angela Zampella; Katrin Fischer; Robert K. Hofstetter; Oliver Werz; Giuseppe Bifulco (Elsevier, 2022)
Here we report the application of a multi-disciplinary protocol for investigating thiazolidin-4-one-based compounds as new promising anti-inflammatory agents interfering with the eicosanoid biosynthesis pathways. The workflow foresaw the generation of a focused virtual library of ∼4.2 ​× ​104 molecules featuring the thiazolidin-4-one core based on the related one-pot synthetical combinatorial route. The built library was initially screened in silico against the microsomal prostaglandin E2 synthase-1 (mPGES-1) enzyme and, afterwards, 23 selected chemical items were synthesized for the subsequent biological screening, applying the one-pot multicomponent synthetic strategy. Preliminary results highlighted the moderate ability of several tested thiazolidin-4-one-based compounds in inhibiting mPGES-1. On the other hand, further computational repurposing investigations were performed on a set of synthesized compounds, highlighting the promising binding of a several items against the soluble epoxide hydrolase (sEH) enzyme, whose inhibition leads to an increase of epoxyeicosatrienoic acids (EETs) that are anti-inflammatory mediators. Three molecules (3, 9 and 21) were able to inhibit sEH featuring IC50 values in the low micromolar range. In order to further profile their anti-inflammatory properties, additional investigations of the three identified hits highlighted their ability to inhibit 5-lipoxygenase (5-LO) and thus to interfere with leukotriene biosynthesis in neutrophils, devoid of activity against cyclooxygenases (COXs) and cytotoxic effects on human monocytes. Our results, obtained by applying a multidisciplinary approach, highlight the thiazolidin-4-one-core as a valuable template for developing novel anti-inflammatory compounds able to synergistically inhibit different targets involved in the arachidonic acid cascade.